EVALUATION OF LABOUR PRODUCTIVITY IN ROAD CONSTRUCTION PROJECTS: A CASE STUDY IN NEPAL - Giri, Om Prakash; Chhimal, Anup (Journal of Civil Engineering, Science and Technology, 2025)
Labour productivity is the most important and multifaceted parameter in the construction sector, serving as a measure of the efficiency and effectiveness of labour resources in completing projects. Despite its significance, the construction industry lacks universally recognised and standardised indicators for assessing labour productivity. This research focuses on determining labour productivity in road construction projects within the Tanahun district of Nepal. In this study, labour productivity in construction activities such as stonework, gabion box filling, soling, PCC, and plum concrete was analysed across four projects using an activity-orientated model measured as output per work hour. Data was gathered over six consecutive days, totalling 24 measurements per activity, with Department of Road Nepal norms serving as benchmarks. Statistical tests, including one-way ANOVA and t-tests, were applied to assess productivity differences across groups. The obtained labour productivity values for skilled and unskilled labour across various construction activities are as follows: Masonry, PCC (M10), PCC (M15), plum concrete, and unskilled labour for soling were found to be 0.76 m3/man-day, 0.28 m3/man-day, 2.39 m3/man-day, 0.789 m3/man-day, 7.734 m3/man-day, 0.858 m3/man-day, 5.446 m3/man-day, 0.777 m3/man-day, 3.875 m3/man-day, 0.416 m3/man-day, and 0.518 m3/man-day respectively. The findings suggest that labour productivity in road construction projects can be improved through timely payment, efficient scheduling, provision of sufficient tools and equipment, effective inventory management, standardised construction techniques, sound financial planning, and provision of adequate breaks. It offers practical strategies to enhance labour productivity in road construction projects and meet productivity standards in the context of developing countries like Nepal.